Draft Annual Plan 1988-89 An Outline for the Approval of State Planning Board Himachal Pradesh - Planning Commission (Planning Commission, 1988)
It would be seen that the total population of 42.81 lakh persons, main workers and marginal workers together constitute 18.14 lakh. Thus the total work force forms 42.37 per cent of the total population. of this work force 13.74 lakh are cultivators and agricultural labourers which constitute 75.74 per cent of the total workers and the rest 24.26 per cent are engaged in other economic activities.
Planning Department, Himachal Pradesh